Silicon containing hybrid copolymers - He, Chaobin; Li, Zibiao (Chemist) (Wiley-VCH, 2020)
This book offers comprehensive and systematic coverage of the latest developments in functional hybrid silicon copolymers, their applications, and how they were developed in relation to previous works in the preparation of various functional groups terminated silicone materials. Silicon Containing Hybrid Copolymers begins with a chapter that introduces readers to organo-silicon materials. It then presents a chapter on reactive functionally terminated polyorganosiloxanes, and contains a section on the methods and advances of functionalized polyhedral oligomeric silsesquioxanes (POSS) and copolymers. Nanostructured self-assemblies from silicon containing hybrid copolymers are discussed?as are superhydrophobic materials derived from hybrid silicon. Other chapters examine silicone copolymers for healthcare and personal care applications; construction of organic optoelectronic materials by using polyhedral oligomeric silsesquioxanes (POSS); and 3D printing silicone materials and devices. The book also includes an overview of material toughening and fire retardancy in regards to hybrid POSS nanocomposites.
Keywords: Silicon polymers.; Copolymers.; elektronické knihy; electronic books